Law for Social Workers. - Brayne, Hugh.; Carr, Helen (Oxford : Oxford University Press, 2010)
This new edition gives a clear and up-to-date picture of how the Children Act 1989 is working. All chapters have been updated with the latest case law, legislation and guidance.
Previous ed.: 2008.
Includes bibliographical references and index.
Keywords: Social workers -- Legal status, laws, etc. -- England; Public welfare -- Law and legislation -- England; Social workers -- Legal status, laws, etc. -- Wales; Public welfare -- Law and legislation -- Wales; Law